Older consumers in the tourism goods and services market - Bałandynowicz-Panfil, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
The aim of this paper is to analyze the impact of demographic processes, with emphasis on an ageing of consumers, on changes in the tourism goods and services market. Two dimensions are considered. First, challenges for tourism market in the perspective of the development (new products, high level of local and international competition). Second, are challenges connected with consumer behaviour changes in an ageing population. The growing importance of older buyers affect the need for intensive adjustment processes on the market and entrepreneurships level. The analysis of literature and statistical data confirmed increasing role of older consumers in tourism: growing purchasing power and greater awareness of consumption needs. New circumstances are significantly affecting the functioning of the tourism market, mainly in developing new products and services to adapt to changes on the demand side of the tourism market. The paper is a contribution to the further considerations of sensitivity of individual sectors in the relation to the demographic processes and consumer behaviour in ageing societies.